Determinants of household food waste in East Kalimantan, Indonesia, based on an urban-rural regression analysis - PUTRI DAULIKA; BERNATAL SARAGIH; MARIYAH MARIYAH (Smujo International, 2026)
Abstract. Daulika P, Saragih B, Mariyah. 2026. Determinants of household food waste in East Kalimantan, Indonesia, based on an urban-rural regression analysis. Asian J Agric 10 (1): g100119. https://doi.org/10.13057/asianjagric/g100119. Food waste is a critical issue affecting environmental quality, economic efficiency, and food security. In East Kalimantan, more than 50% of generated waste is attributed to food waste, yet empirical evidence comparing urban-rural determinants of household food waste in Indonesia remains limited. This study examines the determinants of household food waste across urban and rural settings in East Kalimantan using a quantitative household survey and multiple linear regression analysis. Model significance was assessed using t-tests and F-tests, while explanatory power was evaluated using the coefficient of determination (R²). The results indicate clear contextual differences. In urban areas, household income, food processing practices, and food storage significantly influence food waste. In rural areas, significant determinants include household income, food acquisition methods, and food storage. Notably, income and food storage are consistent predictors in both contexts, whereas food processing is more salient in urban households and food acquisition is more salient in rural households. These findings suggest that food-waste reduction strategies should be context-specific: urban interventions should prioritize consumer education and household expenditure planning, while rural interventions should focus on improving food acquisition efficiency, strengthening local food utilization, and promoting household-based organic recycling to support sustainable food security.